2014
DOI: 10.5830/cvja-2014-043
|View full text |Cite
|
Sign up to set email alerts
|

Thrombolysis risk prediction : applying the SITS-SICH and SEDAN scores in South African patients : cardiovascular topic

Abstract: At present, the only specific medical treatment for acute ischaemic stroke is intravenous administration of recombinant tissue plasminogen activator within 4.5 hours of stroke onset. In the last year, two scores for risk stratification of intracranial haemorrhage have been derived from multicentric European trial groups, the Safe Implementation of Treatment in Stroke – Symptomatic IntraCerebral Haemorrhage risk score (SITS-SICH) and the SEDAN score. The aim of this study was to pilot their use in a cohort of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…[10] Moreover, this score was also validated in African and European population. [17,18,23] For safety reason, the rate of sICH after i.v. rt-PA, as recommended by standard guidelines, should not exceed 7% in certified primary stroke center.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10] Moreover, this score was also validated in African and European population. [17,18,23] For safety reason, the rate of sICH after i.v. rt-PA, as recommended by standard guidelines, should not exceed 7% in certified primary stroke center.…”
Section: Discussionmentioning
confidence: 99%
“…[16] Most of the tool scores have been validated in diverse population, however, the accuracy of the scores is lower than which of the original reports. [10,13,17,18,22,23,33]…”
Section: Discussionmentioning
confidence: 99%
“…Of the four eligible studies, there were no experimental studies; two were retrospective cohort studies [ 41 , 42 ], a prospective cohort study [ 43 ] and a case series study [ 44 ]. Three of the studies reported on thrombolytic therapy using recombinant tissue plasminogen activator [ 42 – 44 ] and the remaining study focused on stroke unit care [ 41 ]. Three of the eligible studies were conducted in South Africa [ 41 43 ] and the other in Morocco [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Despite accounting for confounding factors in the cohort studies, only one study [ 42 ] accounted for it in the analysis. Also, the retrospective nature of two of the cohort studies [ 41 , 42 ], where outcomes were reportedly based on a chart review of medical records, could bias the results by potentially underestimating or overestimating the final outcomes. All included studies contained small and unrepresentative patient samples which limited their generalisability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation